Controllable extracellular biosynthesis of bismuth sulfide nanostructure by sulfate‐reducing bacteria in water–oil two‐phase system. (19th March 2014) - Yue, Lei; Wu, Ying; Liu, Xin; Xin, Baoping; Chen, Shi
<x xml:space="preserve">Abstract</x> Due to strong hydrolysis of Bi3+ as precursor in aqueous media, there are no reports on biosynthesis of bismuth sulfide (Bi2S3) nanomaterials. In this work, the water–oil two‐phase system was used to biosynthesize the Bi2S3 nanomaterials based on the coupling reaction of biological reduction and chemical precipitation process for the first time. The results showed that the water–oil two‐phase system successfully eliminated hydrolysis of the Bi3+ and controllably and extracellularly fabricated the Bi2S3 crystal with high purity. The nanorods with diameter of about 100 nm and length of about 1.0 μm were attained under high dose of lactic acid and SO42−; while low dose obtained the nanobundles consisted of nanoneedles with tip diameter of 10–20 nm and length of about 5.0–10.0 μm. The Bi2S3 nanorods as photocatalyst almost completely degraded methylene blue from solution within 12 h; whereas the Bi2S3 nanobundles removed about 87% of the dye. The amount of the Bi2S3 nanorods decreased by 48% due to photocorrosion, whereas 52% with the nanobundles. The Bi2S3 nanorods had relatively higher photocatalysis activity and slightly stronger photocorrosion resistance than the Bi2S3 nanobundles. © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 30:960–966, 2014